Marked change in blood tacrolimus concentration levels due to grapefruit in a renal transplant patient. (23rd June 2019) - Zhai, Xingyu; Chen, Chaoyang; Xu, Xin; Ma, Lingyue; Zhou, Shuang; Wang, Zhiqi; Ma, Lingyun; Zhao, Xia; Zhou, Ying; Cui, Yimin
Abstract: What is known and objective: Reveal the current status of grapefruit in the Chinese medical environment. Case description: An approximately 2‐fold increase in blood tacrolimus concentration was observed on day 9 in the hospital despite no change in dose. The only possible cause is that the patient had consumed grapefruit during hospitalization, which is often mistakenly considered to be a fruit belonging to the West and uncommon in the medical environment in China. What is new and conclusion: This is the first report of grapefruit‐induced blood tacrolimus concentration change. Chinese medical practitioners should re‐evaluate the impact of grapefruit and food‐drug interactions caused by it. Abstract : This is a case report of increased plasma concentration of tacrolimus in kidney transplant patients due to consumption of grapefruit, a fruit which Chinese people lack understanding of. Chinese medical practitioners should re‐evaluate the impact of grapefruit on Chinese medical environment and enhance patient education of grapefruit juice effect.